Standard and generalized McDonald–Kreitman test: a website to detect selection by comparing different classes of DNA sites - Egea, Raquel (Oxford University Press, 2008)
The McDonald and Kreitman test (MKT) is one of the most powerful and extensively used tests to detect the signature of natural selection at the molecular level. Here, we present the standard and generalized MKT website, a novel website that allows performing MKTs not only for synonymous and nonsynonymous changes, as the test was initially described, but also for other classes of regions and/or several loci. The website has three different interfaces: (i) the standard MKT, where users can analyze several types of sites in a coding region, (ii) the advanced MKT, where users can compare two closely linked regions in the genome that can be either coding or noncoding, and (iii) the multi-locus MKT, where users can analyze many separate loci in a single multi-locus test. The website has already been used to show that selection efficiency is positively correlated with effective population size in the Drosophila genus and it has been applied to include estimates of selection in DPDB. This website is a timely resource, which will presumably be widely used by researchers in the field and will contribute to enlarge the catalogue of cases of adaptive evolution. It is available at http://mkt.uab.es.